Intermittent Compressive Stress Enhanced Insulin-Like Growth Factor-1 Expression in Human Periodontal Ligament Cells - Jittima Pumklin; Jeeranan Manokawinchoke; Kanokporn Bhalang; Prasit Pavasant (International Journal of Cell Biology)
Mechanical force was shown to promote IGF-1 expression in periodontal ligament both in vitro and in vivo. Though the mechanism of this effect has not yet been proved, here we investigated the molecular mechanism of intermittent mechanical stress on IGF-1 expression. In addition, the role of hypoxia on the intermittent compressive stress on IGF-1 expression was also examined. In this study, human periodontal ligament cells (HPDLs) were stimulated with intermittent mechanical stress for 24 hours. IGF-1 expression was examined by real-time polymerase chain reaction. Chemical inhibitors were used to determine molecular mechanisms of these effects. For hypoxic mimic condition, the CoCl2 supplementation was employed. The results showed that intermittent mechanical stress dramatically increased IGF-1 expression at 24 h. The pretreatment with TGF-β receptor I or TGF-β1 antibody could inhibit the intermittent mechanical stress-induced IGF-1 expression. Moreover, the upregulation of TGF-β1 proteins was detected in intermittent mechanical stress treated group. Correspondingly, the IGF-1 expression was upregulated upon being treated with recombinant human TGF-β1. Further, the hypoxic mimic condition attenuated the intermittent mechanical stress and rhTGF-β1-induced IGF-1 expression. In summary, this study suggests intermittent mechanical stress-induced IGF-1 expression in HPDLs through TGF-β1 and this phenomenon could be inhibited in hypoxic mimic condition.